Communism's Jewish Question. Jewish Issues in Communist Archives - Kovács, András (Europäisch-jüdische Studien - Editionen, 2017)
In the last two decades a large amount of previously secret documents on Jewish issues emerged from the newly opened Communist archives. The selection of these papers published in the volume and stemming mostly from Hungarian archives will shed light on a period of Jewish history that is largely ignored because much of the current scholarship treats the Shoah as the end of Jewish history in the region. The documents introduced and commented by the editor of the volume, András Kovács, will give insight into the conditions and constraints under which the Jewish communities, first of all, the largest Jewish community of the region, the Hungarian one had to survive in the time of the post-Stalinist Communist dictatorship. They may shed light on the ways how Jewish policy of the Soviet bloc countries was coordinated and orchestrated from Moscow and by the single countries. The archival material will prove that the ruling communist parties were restlessly preoccupied with the Jewish question. This preoccupation, which kept the whole issue alive in the decades of communist rule, explains to a great extent its open reemergence in the time of transition and in the post-communist period.